Characteristics of Aluminium 7075 Tool Profile for HDPE and PP Welding Against Tensile and Bending - Malisi, Muhammad Sibro; Darsono, Febri Budi; Kriswanto; Alkafi, Abu Faqih; Rochim, Muhammad Nur; Masruhan, Fahmi Irsad (Piston: Journal of Technical Engineering, 2025)
The increasing demand for lightweight materials in the automotive industry has led to the replacement of metal vehicle components with polymers such as High-Density Polyethylene (HDPE) and Polypropylene (PP) to support sustainable development and emission reduction. However, welding dissimilar polymers presents a challenge due to the limitations of conventional techniques. Friction Stir Welding (FSW) emerges as a promising solution by enabling solid-state joining below the melting point. This study investigates the effect of AA7075 tool profile variations—plain cylinder, threaded cylinder, and grooved cone—on the mechanical properties and macrostructure of HDPE-PP FSW joints. Experimental welding was performed at a rotational speed of 2920 rpm and a travel speed of 30 mm/min, with analysis including tensile tests (ASTM D638), bending tests (ASTM D790), temperature measurements, and macrostructural observations. Results show that the threaded cylindrical tool yielded the highest tensile strength (4 MPa) due to effective material flow, while the grooved cone tool produced the highest bending strength (6,8 MPa) through improved vertical and radial mixing. The plain cylindrical tool showed the weakest performance with significant welding defects. Overall, tool geometry significantly influences weld quality, and selection should be based on the mechanical requirements of the application. These findings emphasize the importance of tool design optimization to enhance joint strength and structural integrity in dissimilar thermoplastic FSW.